Fairness, relationships and perceptions of police legitimacy in the context of integrated offender management - Cram, Frederick (Policing and society, 2024)
Integrated Offender Management (IOM) involves the police in England and Wales working closely with other criminal justice agencies to reduce the criminal activities of prolific offenders. The work involves traditional policing methods, but also police officers engaging in meaningful rehabilitative work with IOM participants. However, there may be a tension between aspects of IOM policing and procedural justice theory. Research has shown strong links between citizens’ perceptions of fair treatment and their beliefs about police legitimacy, yet at the same time some IOM policing efforts emphasise hostile and disciplinary practices. These types of approaches can threaten police legitimacy if perceived by citizens as unfair. This paper examines the self-described experiences of people subject to IOM policing. Study findings revealed that, whilst participants viewed aspects of IOM policing as unfair, they broadly accepted the legitimacy of IOM policing. This would run counter to many of the core claims of procedural justice theory. However, one plausible explanation for this reaction lies in the dynamic nature of police legitimacy and its antecedents in IOM. In this context, perceptions of police legitimacy are more firmly grounded in the relational (treatment) dimensions of procedural fairness than in other more decision-orientated aspects of the concept. This reflects the multidimensional nature of procedural justice within which the balance shifts, depending on the criminal justice setting.